Accumulation of geranylgeranylated chlorophylls in the pigment-protein complexes of Arabidopsis thaliana acclimated to green light: effects on the organization of light-harvesting complex II and photosystem II functions - Karlický, Václav; Kmecová Materová, Zuzana; Kurasová, Irena; Nezval, Jakub; Štroch, Michal; Garab, Győző; Špunda, Vladimír (Photosynthesis research, 2021)
Light quality significantly influences plant metabolism, growth and development. Recently, we have demonstrated that leaves of barley and other plant species grown under monochromatic green light (500-590 nm) accumulated a large pool of chlorophyll a (Chl a) intermediates with incomplete hydrogenation of their phytyl chains. In this work, we studied accumulation of these geranylgeranylated Chls a and b in pigment-protein complexes (PPCs) of Arabidopsis plants acclimated to green light and their structural-functional consequences on the photosynthetic apparatus. We found that geranylgeranylated Chls are present in all major PPCs, although their presence was more pronounced in light-harvesting complex II (LHCII) and less prominent in supercomplexes of photosystem II (PSII). Accumulation of geranylgeranylated Chls hampered the formation of PSII and PSI super- and megacomplexes in the thylakoid membranes as well as their assembly into chiral macrodomains; it also lowered the temperature stability of the PPCs, especially that of LHCII trimers, which led to their monomerization and an anomaly in the photoprotective mechanism of non-photochemical quenching. Role of geranylgeranylated Chls in adverse effects on photosynthetic apparatus of plants acclimated to green light is discussed.
Keywords: prenylace; Photosystem II Protein Complex; Chlorophyll; chlorofyl; Light-Harvesting Protein Complexes; světlosběrné proteinové komplexy; Prenylation; adaptace oční; Arabidopsis; fotosystém II (proteinový komplex); Adaptation, Ocular